FUNGSI PERMINTAAN MARSHALLIAN (Marshallian Demand Function) - Priyagus, Priyagus (Faculty of Economics and Business Mulawarman University, 2015)
Request a strategic economic activity, the greater the demand for goods and services by market participants (domestic, foreign governments and the private sector), the economy of a region to be large and growing. Demand curve that describes the behavior of consumers in accordance with the law of demand is derived in many ways, an important one is the Marshallian approach. Through this approach the satisfaction (utility) the consumer is maximized with a certain budget, resulting in the demand functions and graphs are often studied in microeconomics and used in the analysis of the demand for goods and services until nowÂ Keyword: Marshallian, utility, budget dan maksimum